Bridging priorities: Stakeholder preferences, networks, and barriers in road-stream crossing management - Koorosh Asadifakhr; Jingyan Huang; Pauline Perkins; Kevin Lucey; Haiying Wang; Fei Han; Weiwei Mo (PLoS ONE, 2026)
Road-stream crossings (RSCs) represent a critical nexus of infrastructure resilience and ecosystem health, yet fragmented governance and institutional silos hinder effective management. This study used a co-produced survey to assess stakeholder priorities, map the stakeholder collaboration network, and characterize non-financial barriers to RSC decision-making in New Hampshire, USA. Analyses included the Kruskal–Wallis and Dwass–Steel–Critchlow–Fligner tests to evaluate differences in priorities across stakeholder groups, social network analysis to identify central actors, and inductive content analysis for non-financial challenges. Flood vulnerability was the most widely supported goal, offering common ground for collaboration. However, divergences in wildlife conservation, environmental quality, structural risk, and road criticality highlighted persistent tensions between conservation and transportation stakeholders. Socioeconomic goals, including economic impact and environmental justice, received lower ratings and minimal divergence, indicating systemic neglect rather than conflict. Social network analysis identified the New Hampshire Departments of Transportation and Environmental Services as central actors, enabling coordination but concentrating decision power. Content analysis revealed key non-financial barriers: lack of prioritization, project complexity, regulatory burdens, and limited municipal capacity. These findings highlight opportunities for inclusive, multi-benefit decision frameworks, regulatory streamlining, and investments in local technical capacity to better align infrastructure planning with ecological and community needs.